Fc-Elabela mitigates heart failure without liver and renal toxicity in mice - Zhou, Huifen; Gong, Da-Wei; Chen, Ling; Chen, Hui; Wang, Quan; Ullah, Mustajab; Ahmad, Saleem; Jeelani, Ishtiaq; Zhao, Qingbin (Frontiers in Pharmacology, 2025)
AimsElabela (ELA) is a ligand of the APJ receptor and exhibits anti-heart failure activities. However, the short half-life of the ELA limits its clinical applications. Our previous study recombined the short peptide ELA-21 and the Fc fragment of human IgG into a long-acting Fc-ELA-21 fusion protein and has shown that Fc-ELA-21′half-life in mice is 44 h and retained activation of the APJ receptor to exert anti-heart failure activity However, the anti-heart failure mechanisms of Fc-ELA-21 are still unclear, and its optimal dose range and long-term in vivo safety profile remain undefinedThis study aimed to investigate the anti-heart failure mechanisms of Fc-ELA-21, dose range, and in vivo safety.Methods and resultsWe investigated the effects of different doses of Fc-ELA-21 on cardiac function and potential signaling pathways and liver and kidney function by subcutaneous administration of Fc-ELA-21 in mice with myocardial infarction (MI)over 4 weeks. We found that Fc-ELA-21 significantly improved cardiac systolic dysfunction, mitigated pulmonary congestion, slowed down weight gain, activated vascular endothelial growth factor receptor 3 (VEGFR3) and APJ-mediated extracellular signal-regulated kinase (ERK) 1/2 signaling, and promoted endothelial cell proliferation in post-infarct mice. Moreover, the structure and function of the liver and kidney were normal in Fc-ELA-21-treated mice.ConclusionOur results demonstrate that Fc-ELA-21 improves systolic heart failure by activating VEGFR3 signaling and suggest a mechanism for cross-talk between the APJ receptor and VEGFR3 in myocardial infarction MI. Moreover, Fc-ELA-21 is safe in vivo. Hence, the administration of Fc-ELA-21 fusion protein could be a novel therapeutic for systolic heart failure.